Effects of high fiber energy supplements on production performance, milk composition and milk fatty acid profile from dairy ewes fed fresh cut Lolium multiflorum - Miccoli, Florencia Estefania; Perez, Carolina Daiana; Vargas Bello Pérez, Einar; Danelon, José Luis; Cantet, Juan Manuel; Martínez, Rocío; Bargo, Fernando; Colombatto, Darío; Palladino, Rafael Antonio (2022)
Supplementation of dairy ewes under grazing systems can improve milk production but different responses can be obtained when using starch or high degradable fiber as energy sources. The aim of this study was to evaluate the effect of two contrasting sources of dietary energy on animal production, milk composition and fatty acid (FA) profile of dairy ewes fed fresh ryegrass. Ten Pampinta ewes (28 ± 2.3 DIM; 65.8 ± 8.67 kg BW) were assigned to one of two dietary treatments in a complete randomized design with repeated measures: SH (soybean hulls) and CG (corn grain). Daily ration consisted of fresh ryegrass (Lolium multiflorum) plus concentrate in a 50:50 ratio (4% of BW). The experiment lasted 5 weeks, with 3 weeks for data collection. Individual milk samples were analyzed for milk composition and milk FA profile. Data were analyzed in a complete randomized design where supplement was considered a fix effect and ewe the random effect. Dry matter and forage intake were higher in SH (P < 0.05). Milk yield, milk protein and milk fat were similar between treatments. Compared to CG, total polyunsaturated FA (6.77 vs. 4.49 g/100g FA), total n-3 FA (0.89 vs. 0.58 g/100g FA) and total n-6 FA (3.43 vs. 1.94 g/100g FA) were higher in milk from SH (P < 0.05). Results suggest that replacing starch with fibrous supplements in early-lactation dairy ewes constitutes a promising alternative to obtain a more health-promoting FA profile in milk, without compromising milk yield and composition.